Facing the Challenges of Urbanization: Analysis of Service Center Structure in Penajam Village - Putra, Rulliannor Syah; Hidayat, Arief; Jordan, Nadia Almira (Jurnal Planologi, 2025)
Massive urban land use change has emerged as a significant global phenomenon in recent decades, profoundly impacting city morphology, environment, and biodiversity. Uncontrolled urbanization leads to land conversion, alters agricultural livelihoods, and drives the agglomeration and concentration of urban areas. To address these challenges, comprehensive and integrated spatial planning is essential. The urban spatial structure, encompassing the network of facilities and infrastructure, supports socio-economic activities and connects urban centers and sub-centers through transportation networks. Analytical methods such as scalograms, Guttman scales, and centrality indices are employed to determine the structure of service centers. This study identifies service centers in Penajam Village, Penajam Paser Utara Regency, a region experiencing substantial population growth. The objective of this research is to identify service centers and their associated urban area coverage, as well as the availability of facilities within the context of urbanization surrounding the development of the new national capital. This study aims to provide deeper insights into growth dynamics and inform effective urban spatial planning strategies.